Characteristic features of plasma electrolytic treated layers in Na3PO4 solution - Adeleke, S.A.; Bushroa, A.R; Sopyan, Lis (Elsevier, 2017)
Plasma electrolytic oxidation (PEO) treatment of Ti6Al4V (Ti) using various concentrations of Na3PO4 (NAP) has been carried out. Based on the PEO process, characteristics of the treated layers, such as structure, chemical composition, phases, roughness, hardness and porosity level were investigated. Irregular micro-channel spots were found on all treated surfaces. Larger pores were more evident on the PEO treated with NAP-7.5 g/L, and are considered to be related to the high intensity of micro-arc discharges on Ti surface. XRD analyses revealed that the surfaces of treated layers are composed of Ti, TiO6 and anatase. The Profilometry test depicted that the surface roughness of PEO treated layers is significantly higher than bare Ti. The thickness and hardness of PEO-treated layers increased with increasing NAP concentration and found to be highest with sample processed with NAP-10 g/L. Among all the NAP concentration used, 5 g/L showed the least level of porosity. Reflection on the results portends that the PEO treated with 10 g/L concentrations could serve a potential candidate for clinical purposes.